Private Yet Connected: Exploring the Role of Second Instagram Accounts in Online Friendship and Self-Disclosure Among Early Adults - Deffa Adela Putri; Hazhira Qudsyi (Green Publisher, 2025)
This research aims to determine the relationship between online friendship and self-disclosure in early adulthood users of second Instagram accounts. The hypothesis in this research is that there is a relationship between online friendships and self-disclosure in early adulthood users of second Instagram accounts. This research involved 300 early adult respondents aged 18-25 years who had a second Instagram account. Data collection in this research used a questionnaire distributed via online Google Form. The scales used in collecting research data were the Revised Self-Disclosure Scale (25 items, ?=0.852) and the UGM Online Friendship Scale (19 items, ?=0.958). The results of data analysis using the Spearman's Rho correlation test showed that there was a significant positive relationship between online friendship and self-disclosure in early adulthood users of second Instagram accounts (r = 0.469; p<0.001). This shows that there is a significant positive relationship between online friendship and self-disclosure in young adults who use second Instagram accounts.